2020
DOI: 10.1002/jcad.12307
|View full text |Cite
|
Sign up to set email alerts
|

“Meeting Someone at the Edge”: Counselors’ Experiences of Interpersonal Stress

Abstract: Using consensual qualitative research, the authors explored the factors that contribute to counselors’ experiences of interpersonal stress and how counselors respond to interpersonal stressors within therapeutic settings. Thirteen professional counselors representing a variety of counseling contexts and settings participated in semistructured interviews. Through consensus building, the authors identified 4 domains within the data: client characteristics, relationship dynamics, counselor response, and personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Based on this finding, it is possible that professional counselors in this study who were unable to mitigate the effects of posttraumatic stress through self‐care, resilience, and/or coping strategies were more likely to experience posttraumatic stress symptoms. Our finding is consistent with extant research that indicated work‐related stressors were significant predictors of burnout (Henderson, 2013 ; Maslach et al, 2001 ; Moore et al, 2020 ; Mullen et al, 2017 ; Rossi et al, 2012 ) and counselor impairment (Barlow & Phelan, 2007 ; Maslach, 2003 ; Stamm, 2010 ; Stebnicki, 2008 ) while contributing novel findings about how perceived stress during a pandemic affects professional counselors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on this finding, it is possible that professional counselors in this study who were unable to mitigate the effects of posttraumatic stress through self‐care, resilience, and/or coping strategies were more likely to experience posttraumatic stress symptoms. Our finding is consistent with extant research that indicated work‐related stressors were significant predictors of burnout (Henderson, 2013 ; Maslach et al, 2001 ; Moore et al, 2020 ; Mullen et al, 2017 ; Rossi et al, 2012 ) and counselor impairment (Barlow & Phelan, 2007 ; Maslach, 2003 ; Stamm, 2010 ; Stebnicki, 2008 ) while contributing novel findings about how perceived stress during a pandemic affects professional counselors.…”
Section: Discussionsupporting
confidence: 89%
“…The extant body of research has reported the conditions associated with increased counselor stress, and consequently, vicarious trauma, compassion fatigue, and burnout. In a recent study, Moore et al ( 2020 ) conducted consensual qualitative research among a sample of 13 counselors and identified client characteristics (i.e., unpredictability, manipulative, and impulsive), relationship dynamics (i.e., countertransference, intensity, and counselor‐client match), counselor response (i.e., coping and questioning professional judgment and efficacy), and personal versus professional self as factors that contributed to interpersonal stress. Additional studies have linked increased counselor stress and burnout to countertransference management (Choi et al, 2014 ), ethical dilemmas (Henderson, 2013 ; Mullen et al, 2017 ), negative counseling experiences, and professional self‐doubt (Zeeck et al, 2012 ).…”
Section: Counselor Experiences Of Stressmentioning
confidence: 99%
“…That is, as counselors’ years of experience decreased, their self‐reported symptoms of burnout increased. Due to the high stress environments in which prelicensed counselors work, it is likely that their interpersonal stress may affect their personal and professional functioning (Moore et al, 2020). For the prelicensed counselors who are currently engaged in supervision for licensure and the soon‐to‐be graduates who are eligible to pursue licensure as professional counselors, understanding their professional quality of life and affective distress is needed.…”
Section: Prelicensed Counselorsmentioning
confidence: 99%
“…This can be challenging for students because it is in many ways as much a science as it is an art. Furthermore, the work of the counselor may create high levels of relational stress (Moore et al., 2020). Thus, counselor educators must help students develop counseling skills, mitigate relational stress, and learn how to think about counseling in a way that deepens their understanding of relational depth and the interconnectedness in the therapeutic alliance (Knox & Cooper, 2010).…”
Section: Sdmentioning
confidence: 99%